Adrenocortical tumors in children - Ribeiro,R.C. (2000)
Childhood adrenocortical tumors (ACT) are rare. In the USA, only about 25 new cases occur each year. In Southern Brazil, however, approximately 10 times that many cases are diagnosed each year. Most cases occur in the contiguous states of São Paulo and Paraná. The cause of this higher rate has not been identified. Familial genetic predisposition to cancer (p53 mutations) and selected genetic syndromes (Beckwith-Wiedemann syndrome) have been associated with childhood ACT in general but not with the Brazilian counterpart. Most of the affected children are young girls with classic endocrine syndromes (virilizing and/or Cushing). Levels of urinary 17-ketosteroids and plasma dehydroepiandrosterone sulfate (DHEA-S), which are abnormal in approximately 90% of the cases, provide the pivotal clue to a diagnosis of ACT. Typical imaging findings of pediatric ACT consist of a large, well-defined suprarenal tumor containing calcifications with a thin capsule and central necrosis or hemorrhage. The pathologic classification of pediatric ACT is troublesome. Even an experienced pathologist can find it difficult to differentiate carcinoma from adenoma. Surgery is the single most important procedure in the successful treatment of ACT. The role of chemotherapy in the management of childhood ACT has not been established although occasional tumors are responsive to mitotane or cisplatin-containing regimens. Because of the heterogeneity and rarity of the disease, prognostic factors have been difficult to establish in pediatric ACT. Patients with incomplete tumor resection or with metastatic disease at diagnosis have a dismal prognosis. In patients with localized and completely resected tumors, the size of the tumor has predictive value. Patients with large tumors have a much higher relapse rate than those with small tumors.